'It's Knowing the Right Things to Say and Do': Challenges and Opportunities for Trauma‐informed Practice in the Prison Context. Issue 4 (17th September 2019) - VASWANI, NINA; PAUL, SALLY
Abstract: The relevance of trauma‐informed practice (TIP) across the workforce, especially in a trauma‐laden environment such as prison, has gained credence. Little is documented, however, on the practicalities of responding to trauma within custodial institutions where the potential for retraumatisation and the tension between care and control are complicating factors. This article explores the views of over 200 prison staff on the adoption of a trauma‐informed approach for young people in custody. It identifies a gap between vision and practice and, while acknowledging that prisons can become more 'trauma‐aware', disputes the notion that true TIP is possible within current custodial contexts.